Identification of residues that control specific binding of the Shc phosphotyrosine-binding domain to phosphotyrosine sites. - van der Geer, P (1996)
The Shc adaptor protein contains two phosphotyrosine [Tyr(P)]binding modules--an N-terminal Tyr(P) binding (PTB) domain and a C-terminal Src homology 2 (SH2) domain. We have compared the ability of the Shc PTB domain to bind the receptors for nerve growth factor and insulin, both of which contain juxtamembrane Asn-Pro-Xaa-Tyr(P) motifs implicated in PTB binding. The Shc PTB domain binds with high affinity to a phosphopeptide corresponding to the nerve growth factor receptor Tyr-490 autophosphorylation site. Analysis of individual residues within this motif indicates that the Asn at position -3 [with respect to Tyr(P)], in addition to Tyr(P), is critical for PTB binding, while the Pro at position -2 plays a less significant role. A hydrophobic amino acid 5 residues N-terminal to the Tyr(P) is also essential for high-affinity binding. In contrast, the Shc PTB domain does not bind stably to the Asn-Pro-Xaa-Tyr(P) site at Tyr-960 in the activated insulin receptor, which has a polar residue (Ser) at position -5. Substitution of this Ser at position -5 with Ile markedly increased binding of the insulin receptor Tyr-960 phosphopeptide to the PTB domain. These results suggest that while the Shc PTB domain recognizes a core sequence of Asn-Pro-Xaa-Tyr(P), its binding affinity is modulated by more N-terminal residues in the ligand, which therefore contribute to the specificity of PTB-receptor interactions. An analysis of residues in the Shc PTB domain required for binding to Tyr(P) sites identified a specific and evolutionarily conserved Arg (Arg-175) that is uniquely important for ligand binding and is potentially involved in Tyr(P) recognition.